Predictability of Euro area revisions - Katharina Glass (Hamburg University, Department Socioeconomics, 2018)
This study investigates the predictability of revisions to Euro-area major macroeconomic variables using real-time data from the European Central Bank. The application of nonparametric and semiparametric tests enables robust conclusions about the predictability of revisions. Though there is wide evidence of the nonnormality of the distribution function of revision errors, this is the first application of the nonparametric approach to examine revisions. Moreover, to gain robustness, this study performs tests for parameter instability, and includes structural breaks explicitly in the predictability evaluation. The results underline the predictability of Euro area key macroeconomic revisions. Revisions are inefficient and biased, and revision errors are not optimal forecast errors.
Keywords: C8; D80; 330; revision; revision errors; predictability; real-time data; Euro area; unbiasedness; efficiency; news; noise